Pengaruh Pengelolaan Keuangan dan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan Pemerintah Daerah: (Survei pada SKPD di Pemerintah Kabupaten Bandung Barat) - Amalia, Mira; Suwondo, Sulistia (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The quality of financial reports must be considered from preparation to presentation, referring to PP. 71 of 2010 concerning SAP, implementing regional financial management supported by competent HR. This study aims to analyze the effect of Regional Financial Management and HR Competence as independent variables on the Quality of Financial Reports, the dependent variable partially or simultaneously. The population were 31 SKPD, and 73 samples of employees in finance/accounting field in the Regional Government of West Bandung Regency, applying quantitative research with data collection techniques using a questionnaire which tested using multiple linear regression analysis, with SPSS 26.0 application. The conclusions of this study are: (1) Regional Financial Management partially has a positive effect on the Quality of Financial Reports; (2) Competence of HR partially has a positive effect on the Quality of Financial Reports. (3) Regional Financial Management and Competency of HR have a simultaneous positive effect on the Quality of Financial Reports.